A Novel Coordination Polymer Based on Decavanadate Units Linked by Copper(Ii) Ethylenediamine Complexes - Costamagna-Martra, J; Costamagna-Martra, J; Venegas-Yazigi, D; Venegas-Yazigi, D; Hermosilla-Ibanez, P; Hermosilla-Ibanez, P (Wiley-VCH Verlag, 2011)
A novel coordination polymer[{Cu(en)2}(V10O 28)]n · 2n[Cu(en)2(H2O)] · 2n(H3BO3) · 2n(H2O) was obtained by hydrothermal reaction. The compound crystallizes in the monoclinic crystal system, in the C2/c space group, with a = 26.490 (3) Å; b = 11.6558 (11) Å; c = 19.8426 (19) Å; ? = 124.011 (1)°; V = 5078.6(8) Å3. The solid structure is formed by polymeric chains, [Cu(en)2(H2O)]2+ cations, and boric acid and water solvate molecules, stabilized through a multiple hydrogen bond network. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.